2022
DOI: 10.1590/0103-11042022e232
|View full text |Cite
|
Sign up to set email alerts
|

Agrotóxicos, desfechos em saúde e agroecologia no Brasil: uma revisão de escopo

Abstract: RESUMO A presente revisão de escopo objetivou evidenciar o perfil das pesquisas brasileiras que investigam os desfechos em saúde ocasionados pela exposição a agrotóxicos, procurando entender os principais achados, tais como metodologia empregada, tipo de substância, desfechos em saúde, locais investigados, sugestões de ações e diálogo com a agroecologia. Foi utilizada a metodologia ‘scoping review’, seguindo o modelo Prisma-ScR. Entre os 83 artigos encontrados, 61 estudaram os/as agricultores/as e 22 estudaram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
8

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 22 publications
0
5
0
8
Order By: Relevance
“…Thus, our findings agree with the literature. A scope review aimed to highlight the profile of Brazilian research investigating health outcomes due to exposure to pesticides and found that studies point out to positive correlations between exposure to pesticides, hematological outcomes, and genetic damage in the analyzed subjects 12 , which highlights the importance of the association between occupational exposure to pesticides and HN.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, our findings agree with the literature. A scope review aimed to highlight the profile of Brazilian research investigating health outcomes due to exposure to pesticides and found that studies point out to positive correlations between exposure to pesticides, hematological outcomes, and genetic damage in the analyzed subjects 12 , which highlights the importance of the association between occupational exposure to pesticides and HN.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the socioeconomic development of the region, investment in irrigated fruit farming, with an emphasis on large monocultures, brought the need for the intense use of pesticides, a characteristic of its agribusiness production model 12 . According to the 2017 agricultural census, this region comprises 14,306 registered agricultural properties, of which 46% use pesticides 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No Brasil, as políticas de incentivo à produção de commodities é responsável pelo desdobramento do uso de agrotóxicos (Delgado, 2020;Daufenback et al, 2022) e desde 2019, a ANVISA (Agência Nacional de Vigilância Sanitária), que é o agente encarregado pelas análises toxicológicas e o MAPA (Ministério da Agricultura, Pecuária e Abastecimento), que é quem assenta tais elementos, apontaram que cerca de 1.059 agrotóxicos foram registrados e tornaram-se permitidos.…”
Section: A Agroecologia E Seus Desafios Em Tempos De Crises Ambientaisunclassified
“…Além do desenvolvimento socioeconômico da região, o investimento em fruticultura irrigada, com ênfase na monocultura em grandes propriedades, trouxe consigo a necessidade de intensa utilização de agrotóxicos, característica do modelo produtivo do agronegócio 12 . De acordo com o censo agropecuário de 2017, essa região compreende 14.306 propriedades agrícolas cadastradas, das quais 46% empregam agrotóxicos 9 .…”
Section: Introductionunclassified